Taxonomic revision and re-description of Ateuchosaurus pellopleurus (Hallowell, 1861) (Reptilia, Squamata, Scincidae) with resurrection of A. okinavensis (Thompson, 1912) - Tomohisa Makino; Takafumi Nakano; Taku Okamoto; Tsutomu Hikida (Zoosystematics and Evolution, 2023)
The scincid lizard Ateuchosaurus pellopleurus (Hallowell, 1861) has been recognized as a single species widely distributed in the Osumi, Tokara, Amami, and Okinawa Groups of the Ryukyu Archipelago, southern Japan. However, a recent molecular phylogenetic study suggested that this skink should be divided into two species: one distributed in the Osumi to Amami Groups, and another distributed in the Okinawa Group. For A. pellopleurus, two extant syntypes collected from an island of the Amami Group were confirmed. Therefore, we identified the species in the Osumi to Amami Groups as A. pellopleurus sensu stricto by designating one of the syntypes as the lectotype for this species. For the species in the Okinawa Group, we resurrected A. okinavensis (Thompson, 1912), of which the type locality is on Okinawajima Island in the Okinawa Group. Ateuchosaurus pellopleurus and A. okinavensis can be differentiated by the following characteristics: usually separated frontonasal and frontal, 8–14 subdigital scales on the fourth toe (mode = 11), and usually two or three pairs of dorsal median scale rows with black stripes in A. pellopleurus; usually fused frontonasal and frontal, 10–16 subdigital scales on the fourth toe (mode = 13), and usually no stripe on the dorsal scales or a pair of dorsal median scale rows with black stripes in A. okinavensis.